A flashing success: A community-engaged approach to finding western U.S. fireflies - Christy Bills; Gavin Martin; Ellen Eiriksson; Arthur Morris; Alexandra G. Duffy; Seth M. Bybee (PLoS ONE, 2026)
Fireflies are well-documented in many regions of the USA. However, the presence of flashing fireflies in much of the western United States remains largely unknown. Leveraging citizen science, this study aimed to locate populations of bioluminescent fireflies across Utah. Through a multifaceted public outreach campaign and an interactive website for data collection, citizen scientists were invited to report firefly sightings. Over nearly a decade, the project successfully amassed reports from diverse locations, significantly expanding the known distribution of bioluminescent fireflies in Utah and beyond. Validation of reports was conducted through on-site observations and specimen collection. Despite challenges in data reports (e.g., reports from outside desired area) and public interest management (e.g., protecting private property sites), the project achieved remarkable success, with over 135 unique localities documented. Media coverage, social media engagement, and educational outreach further amplified the impact of the project. Limitations in data quality and public engagement were addressed through iterative improvements in reporting protocols and outreach strategies. Future directions include expanding the project to encompass the western United States and exploring innovative communication strategies. By partnering with organizations in neighboring states, the project aims to create a robust dataset and foster public awareness of these charismatic invertebrates. This study highlights the effectiveness of community-engaged approaches in biodiversity research and underscores the importance of public involvement in scientific endeavors.